AB1097 Patients' experiences of remote monitoring of rheumatoid arthritis using a smartphone app. (15th June 2017) - Austin, L; Sanders, C; Dixon, W
Abstract : Background: The care of patients with Rheumatoid Arthritis (RA) is guided by monitoring changes in disease activity. However, whilst a number of patient-related outcome measures (PROMS) exist 1, they are not collected on an on-going basis. Consequently, there are few objective measurements of disease activity, between clinic visits, to inform treatment decisions. In response to this, the REMORA study (RE mote MO nitoring of R heumatoid A rthritis) is developing a smartphone app, to capture data on disease activity and integrate it directly into the electronic patient record. The project explores whether on-going collection of electronic patient-reported outcomes (ePROS) between clinic visits can enhance clinical care, support patient self-management, and provide a sustainable source of data for research. Objectives: To describe patients' experiences of remote monitoring of their disease activity, and the perceived value in relation to clinical consultations and self-management. Methods: A diverse sample of 20 patients with RA entered data into the app over a three month period in response to daily, weekly and monthly question sets (table 1). An optional diary component was included, but not integrated into the EPR. The ePROS had been determined during earlier interviews with rheumatology patients, practitioners and researchers. Qualitative interviews were conducted with patients at the end of the three month period. Interviews explored patients' views on the components of the app, and perceived implications for self-management and clinical care. Interviews were transcribed and analysed thematically. Results: Qualitative analysis of the data identified a number of themes including; the benefits and limitations of using scales to reflect changes in symptoms experienced, the value of the diary for providing contextual information and an "outlet" for feelings, and the impact the data made to their clinical consultation and self-management. Overall, the collection of longitudinal data was seen as useful by patients. Successful integration with the EPR allowed data to be displayed graphically during clinical consultations. Reviewing remote monitoring data detected changes which may otherwise have been missed such as flares in disease, or gradual improvements in response to new treatments. Data therefore facilitated " a shared conversation " and decision making around treatment plans. Additionally, being able to self-reflect on data recorded enabled patients to identify triggers and alleviators in relation to their disease activity and take steps to self-manage their RA; for example, by recognising when they needed to rest as opposed to "just carrying on" when their symptoms were more severe. Conclusions: The app was well received by patients and feedback suggests that the ePROS recorded can capture changes in disease activity in a manner that is meaningful to patients and facilitates both clinical consultations and self-management. References: http://oml.eular.org/Toolbox of Patient Reported Outcomes. Acknowledgements: . Disclosure of Interest: None declared